Spatial Inequalities in Early Childhood Developmental Vulnerability and Education and Care Provision Across Australian Local Government Areas - Li, Shurong (Transactions on Social Science, Education and Humanities Research, 2026)
This article combines the data of the 2021 Australian Early Development Census with educational and nursing service records, regional socio-economic indexes, national quality standard ratings and public transportation accessibility measures. This study analyses the vulnerability of early childhood development and education and nursing in Australian local government areas (LGAs). This article uses descriptive statistics and visual analysis to assess whether the service capacity, quality and accessibility meet the local development needs. The results show that LGAs, which has a higher proportion of vulnerable children in two or more fields, tends to have greater socio-economic disadvantages and poorer public transportation accessibility. Compared with the child population, these local governments tend to have lower service capacity and a smaller proportion of high-rated services. In many highly vulnerable local government areas, inadequate capacity, quality and transportation exist at the same time, indicating that developmental vulnerability is correlated with overlapping space and service inequalities, rather than a single form of disadvantage. However, some highly vulnerable areas did not show substantial service barriers, indicating that broader socio-economic and community conditions also contributed to development outcomes. The results of the study support a local-based policy approach and help to combine service expansion, quality improvement, transportation assistance and broader socio-economic support in future practice. Because the analysis is descriptive and based on aggregated LGA-level data, the identified relationships should not be interpreted as causal.